2021
DOI: 10.3390/app11146508
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Analysis of Biological Signals with the 0–1 Test: A Case Study of the PhotoPlethysmoGraphic (PPG) Signal

Abstract: The 0–1 test distinguishes between regular and chaotic dynamics for a deterministic system using a time series as a starting point without appealing to any state space reconstruction method. A modification of the 0–1 test allows for the determination of a more comprehensive range of signal dynamic behaviors, particularly in the field of biological signals. We report the results of applying the test and study with more details the PhotoPlethysmoGraphic (PPG) signal behavior from different healthy young subjects… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
(58 reference statements)
1
5
0
Order By: Relevance
“…Because of averaging such a large time window, these dynamic collateral behaviors, whose physiological impact is evident, are masked. Nevertheless, this study reinforces the hypothesis already suggested in previous works [9,10] of the multi-dynamic (multiscale) character present in the PPG signal. In some way, this dynamic multiscalability confirms the information transfer from large to small timescales, whereby a wide variety of subsystems contribute to the regulatory mechanisms of the cardiovascular system.…”
Section: B Ppg Signals Dynamic Discrimination Experimentssupporting
confidence: 92%
See 4 more Smart Citations
“…Because of averaging such a large time window, these dynamic collateral behaviors, whose physiological impact is evident, are masked. Nevertheless, this study reinforces the hypothesis already suggested in previous works [9,10] of the multi-dynamic (multiscale) character present in the PPG signal. In some way, this dynamic multiscalability confirms the information transfer from large to small timescales, whereby a wide variety of subsystems contribute to the regulatory mechanisms of the cardiovascular system.…”
Section: B Ppg Signals Dynamic Discrimination Experimentssupporting
confidence: 92%
“…The generated signals contain 150,000 points or observations (samples). Their dynamic congruence was verified using a previously formulated procedure [10]. The spectrum of dynamical behaviors could exhibit most of the dynamical behaviors found in the phenomena of the natural world, except for the fruitful dynamism present in the dynamical transitions between stable regimes.…”
Section: ) Reference Signals (Synthetic Dataset)mentioning
confidence: 93%
See 3 more Smart Citations